The Structure and Dynamics Argument against Materialism Revisited - Mărăşoiu, Andrei (Problemos, 2020)
Alter (2016) elaborates and defends an ambitious argument advanced by Chalmers (2002) against physicalism. As Alter notes, the argument is valid. But I will argue that not all its premises are true. In particular, it is false that all physical truths are purely structural. In denying this, I focus not on the objects of pure physical theory but on the homely, macroscopic objects of our daily lives.